Speeding up for a son? Fertility transitions among Asian migrants to Canada - Alícia Adserà; Ana M. Ferrer (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2016)
We use the 2001 and 2006 Canadian Census to study how the sex-ratios at second birth, conditional on both the spacing between the first two children and the gender of the first, vary across place of birth or religious affiliation. We find that South Asian women give birth to a higher proportion of boys after a first-born girl compared to both natives and other immigrant groups with girls and also to South Asians with a first-born boy. Across religious groups, Sikhs present a similar behavior. These abnormal sex-ratios are particularly skewed when the time span between the first two births is short. This clearly indicates that sex-selective abortion happens more frequently after conceptions that occur fairly close to the birth of a first girl. Sex ratios return (close) to normal for these groups if live-births are spaced three years or longer.
Keywords: 330